Low-cycle fatigue investIgation by acoustIc emission method - SIEDLACZEK, J.; PILECKI, S.; DUŠEK, F. (Archives of Acoustics, 1990)
The results of the measurements of acoustic emission (AB) count rate are presented during low-cycle fatigue of the variously heat treated 45HNMFA structural steel, which can be used for the production of high-pressure chambers. The experimental technique is described briefly. The most important result of this investigation is the occurrence of three stages of the AB activity during the low-cycle fatigue. These dependencies can be applied in monitoring of the service life (safe exploitation period) of high-pressure chambers and/or other studied objects.